Central Asia and China: cooperation in the field of ecology and environment - Омaровa, М. А. (Journal of Oriental Studies, 2018)
Since the declaration of independence, the countries of Central Asia as full members of the international community, on the basis of equality of mutual benefit, develop relations with the states of the world. The development of multilateral ties with China is one of the priorities of the foreign policy of Central Asia. Relationships for a quarter of a century from simple trade have grown to the level of strategic partnership. Despite the fact that bilateral and multilateral relations have reached a high level of development, due to various political and economic factors there appear new problems. Among them, the problem of environmental protection and environmental protection is acute. Attempts to implement projects that are strategically important for the state sometimes lead to situations that are contrary to the interests of neighboring countries.